Attractive dispersion interactions versus steric repulsion of tert-butyl groups in the crystal packing of a D3h-symmetric tris(quinoxalinophenanthrophenazine) - Kohl, Bernd; Bohnwagner, Mercedes V.; Rominger, Frank; Wadepohl, Hubert; Dreuw, Andreas; Mastalerz, Michael (Chemistry - a European journal, 2016)
The crystalline packing of a π-extended D3h-symmetric triptycene reveals a particular π stacking motif with an almost-eclipsed arrangement of adjacent π planes despite the steric repulsion of tert-butyl substituents. Four model compounds were analyzed by using single-crystal X-ray diffraction and theoretical calculations to study the influence of dispersion interactions of molecular parts and understand the relationship between the molecular structure and this unique packing motif.